Contextualising Fregellae: Local Interests in a “Globalised” Mediterranean - Ricci, Luca (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The article employs the Latin colony of Fregellae as a case study to overcome the communis opinio that colonial settlements were parva simulacra Urbis (Gell. XVI.13.9). In particular, the colony, initially founded by Rome in the context of the Second Samnite War, could move away from the Urbs and develop localised interests. Such interests could be explained through a dynamic contact between colonists and local populations, thus forming a variegated social landscape which did not necessarily display cultural similarity with Rome. Similarly, the cityscape could be employed to ascertain how certain colonies chose architectural solutions which took into account localised needs. It is in this context that the article will examine the alliance between Fregellae and Rome in light of the Second Punic War. Traditionally interpreted as a demonstration of blind loyalty, the article will put forth the idea that the colony could decide its alliances in view of potential benefits, which, in the case of Fregellae, were manifested in the economic and military advantages reaped in the eastern Mediterranean. Interestingly, these benefits affected the colony and, more specifically, its architectural facade, as seen in the building activity carried out in the period immediately after the endeavours in the East.